Changes in the Antioxidant Properties of Quince Fruit (Cydonia oblonga Miller) during Jam Production at Industrial Scale - María V. Baroni; Joaquín Gastaminza; Natalia S. Podio; Mariana S. Lingua; Daniel A. Wunderlin; Jose L. Rovasio; Roberto Dotti; Juan Carlos Rosso; Silvina Ghione; Pablo D. Ribotta (Journal of Food Quality)
The content of phenolic compounds and their relationship with the antioxidant capacity of quince fruit were evaluated before and after jam processing at industrial scale. Waste samples from industrial processing were also analyzed. Twelve phenolics and one organic acid were identified and quantified by HPLC-DAD-QTOF. According to the results, jam processing did not produce a decrease in polyphenolic content, and, in some cases, the polyphenolic content even increased. Antioxidant capacities determined by DPPH and FRAP assays showed similar results. On the other hand, the waste samples analyzed retained large amounts of polyphenols, even though their antioxidant capacity was lower than that in pulp samples. Boosted Regression Trees analysis showed a good correlation between phenolic profile and antioxidant capacity, with 5-p-coumaroylquinic acid being the most relevant compound to explain the antioxidant capacity by both methods.